2020
DOI: 10.7883/yoken.jjid.2019.411
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Age is not a Risk Factor for Mortality in Patients with Bacteremia Caused by Extended-Spectrum β-Lactamase-Producing Organisms: a Multicenter Cohort Study

Abstract: A 5-year multicenter retrospective cohort study was conducted across six hospitals in Niigata, Japan. Patients (n = 179) with bacteremia due to ESBL-producing organisms were included in the study. The rate of appropriate carbapenem prescription was 41 (61%) in patients aged 65-84 years and 31 (89%) in those aged ≥85 years; patients aged ≥85 years were significantly more like to receive a carbapenem than their younger counterparts. After propensity score matching, 65 patients were assigned to two groups based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
2
0
0
Order By: Relevance
“…It can be predicted that methods to reduce unnecessary antibiotic use, such as the implementation of rational antibiotic management programs and national planning to restrict antibiotic use, will contribute to decreasing antibiotic resistance and the reduction of the mortality rates of BSI in the ICU in the future. The 28-day mortality rate in this study was consistent with other studies (2)(3)(4)9,16,17). No studies in the literature show the 3-day mortality rate, but Evans et al (2), and Hattori et al (3) reported 7-day mortality rates of 6.7% and 11%, respectively.…”
Section: E a R L Y A C C E S Ssupporting
confidence: 90%
See 1 more Smart Citation
“…It can be predicted that methods to reduce unnecessary antibiotic use, such as the implementation of rational antibiotic management programs and national planning to restrict antibiotic use, will contribute to decreasing antibiotic resistance and the reduction of the mortality rates of BSI in the ICU in the future. The 28-day mortality rate in this study was consistent with other studies (2)(3)(4)9,16,17). No studies in the literature show the 3-day mortality rate, but Evans et al (2), and Hattori et al (3) reported 7-day mortality rates of 6.7% and 11%, respectively.…”
Section: E a R L Y A C C E S Ssupporting
confidence: 90%
“…It has been stated in many publications that CCIS and APACHE II scores were useful in 28-day mortality estimations in BSI (3,8,9,12,15,16). We found that both high APACHE II scores and CCIS were risk factors for 3-day and 28-day mortality.…”
Section: E a R L Y A C C E S Ssupporting
confidence: 51%